2011
DOI: 10.1093/europace/eur194
|View full text |Cite
|
Sign up to set email alerts
|

The cost of illness of atrial fibrillation: a systematic review of the recent literature

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia, its prevalence increasing markedly with age. Atrial fibrillation is strongly associated with increased risk of morbidity, including stroke and thromboembolism. There is growing awareness of the economic burden of AF due to ageing populations and constrained public finances. A systematic review was performed (1990-2009). Cost studies for AF or atrial flutter were included; acute-onset and post-operative AF were excluded. Total, direct, and indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(142 citation statements)
references
References 49 publications
(71 reference statements)
2
130
0
10
Order By: Relevance
“…Consistent with previous published cost of illness of atrial fibrillation 13 , hospitalization cost for the treatment of stroke was the major driver of overall cost in this review. Our study found that the median LOS in hospitals for stroke patients with AF was estimated to be 15.5 days.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with previous published cost of illness of atrial fibrillation 13 , hospitalization cost for the treatment of stroke was the major driver of overall cost in this review. Our study found that the median LOS in hospitals for stroke patients with AF was estimated to be 15.5 days.…”
Section: Discussionsupporting
confidence: 86%
“…Due to the limited information provided in the reviewed studies, it is difficult to further explore the relationship between medical costs and time horizon. Lastly, compared with other costs of illness systematic reviews for AF 13 and other diseases 46,47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Общие затраты на терапию одного пациента с ФП в год достаточно высоки и составляют в США $2000-14200, а в странах Европы -€450-3000, что сопо-ставимо с затратами на терапию сахарного диабета (€5262 в Германии) и стабильной стенокардии ($4949 в США) [13]. Прямые затраты на ФП в Великобрита-нии в 2000 г. достигли 0,9-2,4% от бюджета системы здравоохранения [13].…”
Section: результаты и обсуждениеunclassified
“…42 Most of the costs associated with the complications of AF are due to hospitalization; a systematic literature review estimated that hospitalization represented 50%-70% of the annual direct costs of AF. 43 …”
Section: 31mentioning
confidence: 99%